Investigation of PVA Matrix Hydrogel Loaded with Centaurea cyanus Extract for Wound Dressing Applications: Morphology, Drug Release, Antibacterial Efficiency, and In Vitro Evaluation - Ucar, Melis Abahuni; Gul, Enis Muhammet; Uygunoz, Deniz; Derun, Emek Moroydor; Piskin, Mehmet Burcin (MDPI, 2025)
A polyvinyl alcohol (PVA) matrix hydrogel loaded with Centaurea cyanus extract was created for transdermal wound healing. Secondary metabolites, antibacterial properties, and the cytotoxicity of C. cyanus extract were investigated. The secondary metabolite profiles of the extract were determined by liquid chromatography-mass spectrometry (LC-MS) technique. It was determined that the extract has metabolites such as quinic acid, caffeoylquinic acid, kaempferol, etc., which contribute to the steps of wound healing. The extract had significant activity against Staphylococcus aureus when compared with ampicillin antibiotic and showed an inhibition zone of 16.9 mm +/- 0.8, whereas ampicillin's inhibition zone was 15.8 mm +/- 0.8. The extract did not exhibit cytotoxic effects on 3T3-L1 (CL173) healthy skin fibroblasts, maintained cell viability for 72 h, and exhibited a 19% proliferative effect. Fourier-transform infrared spectroscopy, scanning electron microscopy, ultraviolet visible spectrophotometer, tensile strength analyses, in vitro release, and physicochemical tests were conducted. It was seen that the surfaces of the samples are smooth and homogeneous, patches had a significant amount of water absorption capacity, and 79% of the extract was released within the first 24 h of application; consequently, these results indicate that C. cyanus might be used in wound healing with its antibacterial, growth-promoting properties.
Keywords: Centaurea cyanus; hydrogel; wound dressing; polyvinyl alcohol; HYPERICUM-PERFORATUM; PHENOLIC-ACIDS; IDENTIFICATION; L.; FLAVONOIDS; QUERCETIN; VIVO; MSN; Polymer Science